ANALISIS FAKTOR-FAKTOR KINERJA KEUANGAN YANG MEMPENGARUHI MARKET SHARE PERBANKAN SYARIAH DI INDONESIA - Deby Aryanti Lasrin (2021)
This research is a quantitative study aimed to find out whether there is an effect between financing risk, profitability, and capital on market share. The object of this research is Islamic Commercial Bank Companies (BUS) listed on the Financial Services Authority (OJK) for the period 2015-2019. The sample in this study was determined using a saturated sampling method. Data analysis in this study using Microsoft Excel 2016 and hypothesis testing using panel data regression analysis with a significant level of 5% (0.05) and assisted by the program E-Views 10. The result obtained in this research are (1) Financing Risk has a negative effect on Market Share, (2) Profitability has no effect on Market Share, (3) Capital has a positive effect on Market Share.